Risk indicators for syndromic and nonsyndromic orofacial clefts in Southern Province of Saudi Arabia - Bandar Alyami; Mutaz Ali-Hassan; Manasaour Al-Mahri; Fahad Alyami; Saeed Alharieth (Wolters Kluwer Medknow Publications, 2019)
Objective: This study was designed to find out risk indicators for the development of orofacial clefts (OFCs) in the Southern Province of Saudi Arabia. Materials and Methods: This was a retrospective study carried out in a maternity hospital from January 2013 to December 2016. Data including child sex, type and site of cleft, birth weight and birth month (season), parents' age at the time of their child's birth, paternal and maternal habits, parental consanguinity, and family history of OFCs were obtained. The data were processed and analyzed using SPSS software, Version 20. Results: Overall prevalence of OFCs in the study population was 0.65/1000 live births. There were 10 males, 5 females, and 1 ambiguous sexual orientation. Of the 16 OFC patients, 9 (56.25%) were classified as having syndromic OFCs (SOFCs) and 7 (43.75%) as having non-SOFCs (NSOFCs). Cleft lip and cleft lip/palate both had strong family history of OFCs. Similarly, the phenotype of OFCs and the presence of syndromic or NSOFCs did not show a relationship with paternal smoking habits during pregnancy. No relationship was reported between parental consanguinity with the presence of these factors. However, results showed that 13 (81.3%) out of 16 identified cases of OFC had background consanguinity. Conclusion: Prevalence of OFC in the current study was within reported range, consanguinity was observed in 81.3% of identified cases. Further research is paramount in the role of consanguinity in OFC in Arabian population.